Pathophysiological Significance of Urea in Glomerular Filtration Dysregulation in Hepatorenal Syndrome: An Integrative Review - Gozhenko, Anatoliy; Zukow, Walery; Gozhenko, Olena; Kvasnytska, Olga (Journal of Education, Health and Sport, 2025)
Objective: To conduct an integrative review of the pathophysiological significance of urea in glomerular filtration dysregulation in hepatorenal syndrome (HRS), synthesizing heterogeneous evidence from experimental, clinical, and translational studies using the five-stage Whittemore & Knafl methodology. Methods: A systematic literature search was performed in PubMed/MEDLINE, Embase, Cochrane Library, Web of Science, Scopus, and Ukrainian scientific databases covering 1900–2024. Search terms combined “hepatorenal syndrome,” “urea,” “uremic toxins,” “glomerular filtration,” and “pathophysiology.” Two independent reviewers selected studies and assessed quality using CASP and JBI criteria. Results: A total of 227 relevant studies were analyzed, including 89 experimental, 76 clinical, 34 reviews, and 18 meta-analyses. Five main thematic categories emerged: mechanisms of urea accumulation (notably GFR reduction to 10–20% of normal in HRS), toxic effects via protein carbamylation (correlation r=0.947, p<0.001), oxidative stress and inflammatory reactions, formation of pathophysiological vicious cycles, and therapeutic strategies. Contributions from the Ukrainian scientific school notably advanced the understanding of HRS as a systemic disease with urea as a central pathophysiological mediator. Conclusions: Urea plays a central role in HRS pathophysiology as an active mediator, not merely a passive marker of renal dysfunction. Elevated urea levels above 35 mmol/L associate with a 3.42-fold increased mortality risk, while reductions exceeding 30% correlate with improved clinical outcomes, emphasizing the need for randomized trials targeting urea correction in HRS. Professor A.I. Gozhenko’s Hypothesis on Urea Regulation Professor Gozhenko fundamentally revises the traditional view of urea, proposing it as an active regulatory metabolite with critical homeostatic functions rather than a mere metabolic waste product. Blood urea concentrations (5–8 mmol/L) are comparable to glucose levels and far exceed creatinine concentrations, indicating its physiological importance. The strict homeostatic regulation of urea levels supports its role in maintaining water-electrolyte balance and renal blood flow. Urea exerts concentration-dependent effects: beneficial at physiological ranges and potentially harmful when elevated. This insight highlights renal self-regulation mechanisms that act preventively to maintain organismal homeostasis before systemic signals intervene. Given the enormous daily glomerular filtration volume (~175 liters), even minor tubular reabsorption disturbances could cause significant fluid loss, underscoring the critical importance of these autoregulatory processes. Although homeostasis and urea are integral elements of the comprehensive regulation of water-salt metabolism, their dysregulation can cause significant clinical problems. Notably, previous reviews on sodium regulation also form parts of this broader issue of water-electrolyte balance regulation, emphasizing the complexity and interdependence of mechanisms sustaining homeostasis. Clinically, this paradigm shift suggests interpreting urea levels as active regulatory biomarkers, opening new avenues for personalized therapies targeting optimal urea homeostasis, preventive interventions, and novel treatments for kidney and liver diseases. Future research should focus on elucidating molecular mechanisms of urea’s regulatory functions, defining optimal concentration ranges in pathology, and developing targeted therapeutic strategies based on these concepts.